Judo combat time, scores, and penalties: Review of competition rules changes between 2010 and 2020 (Revista de Artes Marciales Asiáticas, 2022)
This study aimed to describe and analyze the main changes in the official competitive rules of judo between 2010 and 2020, highlighting changes in combat time, scores and penalties. In this retrospective study, a search was performed for official documents which regulated judo rules between 2010 and 2020 on the websites of the International Judo Federation and the Brazilian Judo Confederation, as well as refereeing manuals of the Sergipe Judo Federation (Brazil) and on the Google platform. Over the years, regular combat time has been shortened (2015=5’->4’ for women; 2017=5’->4’ for men), as well as osaekomi time (2013=25”->20”). This change was intended to facilitate the public’s understanding of judo scores, as well as to devalue the use of penalties to achieve the victory (2010=koka’s exclusion; 2013=penalty was no longer worth scores; 2017=yuko’s exclusion, shido no longer decided the winner in regular time; 2018=shido no longer decided the golden score winner). Attack actions were encouraged (ban on actions to flee combat) and there was an intention to reduce the risk of injuries in competitive judo (prohibition of some types of actions and grips). In other words, there was an attempt by the International Judo Federation to encourage positive judo through the rules from 2010 to 2020. However, these constant rule changes made the competitive training context unstable. Judo coaches and athletes must be aware at the end of each Olympic cycle for new changes which will eventually be introduced and adapt to them quickly to achieve high performance.